Fatigue behavior of hybrid eco-composites: A review. (2023) - Krishna Teja, J.M.; Chris Doel Biju, P.; Goutham Sai Aditya Varma, Ch.; Kumar, R.R.; Singh, D.; Gaur, P.
Abstract: Multifunctionality of composites has gained popularity, primarily through the hybridization of polymer composites for augmented performance. In this case, hybridization is ensured by adding fibrous reinforcement of different materials. There are a multitude of characteristics which can be enhanced due to hybridization. The synthetic reinforcements respond to uncontrolled carbon footprints, so we cannot claim them as sustainable. Hence, scientists have been discovering new solutions in sustainable eco-composites (with natural reinforcements) to tackle the environmental challenge. It is reported that albeit the natural fibres are eco-friendly, but they often lack in desired properties and hence find difficulty to enter the market. To achieve desired properties, several limitations of natural fibre, such as hydrophilic qualities, can be addressed by different surface alterations and chemical treatment procedures. Post the fourth industrial revolution, the rising concern about environmental issues has led an increased interest in natural fibre hybrid composites (also called as hybrid eco-composites). Such composites are composed of eco-friendly fibres or a combination of synthetic and natural fibres as a reinforcing material which makes it capable for multifunctional applications. Natural fiber reinforced composites have a great potential of cost per unit weight reduction and renewability over applications such as door panel, seat backs, dashboard, noise insulation panel, railing, bridge, and roof tiles. The prior art reveals that these composites have low fatigue strength which limits itself in structural application in comparison to its competitors, the synthetic composites. This means hybridization could result in synergy of advantages of each of the constituents leading to high fatigue strength, better load carrying, eco-friendly, and a low-cost structure. This review provides an overall insight on various hybrid eco-composites including their mechanical properties, fatigue behavior and its applications.